Akibat Hukum Peralihan Hak Atas Saham Berdasarkan Pembatalan Akta Hibah; Studi Kasus Putusan Peninjauan Kembali No 53/Pk/Tun/2014 Tanggal 12 Agustus 2014 - Nadhira Amaliah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study raises legal issues regarding changes in the composition of limited liability company shareholders which are not in accordance with applicable laws and regulations. The background to the problem is the drafting of the Meeting's Decree regarding changes in the composition of shareholders based on the authority of the parties in acting. The parties based their authority on the Declaration of Decision which canceled the deed of share grant, in which this Decision was a reference to the deed making. Therefore problems arise regarding the validity of the transfer of rights to shares based on the cancellation of the grant and the legal consequences of the transfer of rights to shares based on the cancellation of the grant.Keywords: Changes in the Composition of Shareholders, Cancellation of Deed of Grant, Decision on Declaration